Analisis Level Berpikir Berdasarkan Taksonomi Solo pada Materi SPLDV Siswa Kelas VIII di SMP Negeri 1 Waikabubak - Ghunu, Yosefina; Making, Samuel Rex Mulyadi; Lede, Yulius Keremata; Lubur, Dorothea Novia Ludo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the level of thinking based on the SOLO Taxonomy on linear equation materials (SPLDV) among eighth-grade students at SMP Negeri 1 Waikabubak. The type of research used is descriptive research with a qualitative approach, and the subjects of this study are the eighth-grade students of class VIII B at SMP Negeri 1 Waikabubak, while the object of this research is the students' level of thinking in solving SPLDV story problems based on the SOLO Taxonomy. Data collection was conducted using written tests, interviews, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing stages. Based on the results of the data analysis obtained, it can be concluded that the level of thinking of students on SPLDV materials based on the SOLO Taxonomy reaches different levels. According to the research results, the percentage of test results for the level of thinking of eighth-grade students class VIII B at SMP Negeri 1 Waikabubak indicates that students fall into the high category 64% of the students are in the high category, while 29% are in the medium category, and 7% are in the low category.